Sistem Pendukung Keputusan Kenaikan Jabatan Pada PT. Bogowonto Primalaras Menggunakan Metode Profile Matching Berbasis Web - Haris Ihsanil Huda; Ahmad Asifuddin; Zaenal Mustofa (STEKOM PRESS, 2021)
One of the main factors in achieving effective and efficient performance isattention to human resources. Having reliable and truly appropriate human resourceswith needs is the hope of every manager. The company needs employees with the appropriate abilities with job roles. As for the position of PT. Bogowonto Primalaras still uses a work period limit where employees cannot fill vacant positions at any time, based on the criteria of tenure an employee fulfills the term of service that is in accordance with his expectations. where on assessment in absenteeism is carried out by collecting daily report data that makes HRD send one by one who has sent the daily report. Where is the report related to the productivity criteria of an employee who has reached the target or not.